Efecto de la actividad de agua y la modificación de la atmósfera gaseosa sobre la producción y calidad de conidios de Beauveria bassiana - Núñez Gaona, Óscar (Universidad Autónoma Metropolitana, 2009)
Biological control is defined as the reduction of pest populations using natural enemies, Beauveria bassiana is wildely distributed in nature, has a potential to control nearly of 70 pests of insects, this feature has increased the interest for industrial production, in fact in many places of the world there are commercial formulations based on Beauveria bassina. Produces a different kind of conidia, depending on culture conditions. The method used for conidia production affects bioinsecticide activity of fungus, and the main production methods are solid state fermentation, which is defined as microorganism grown on moisted solid substrates with enough water to allow metabolisms, with no water leakeage and with air as continue phase. Other culture method is a biphasic system, in which inoculum is produced in liquid media, followed by a solid production medium, in both production systems the desirable product are conidia. Composition effect was evaluated using four media: Sabouraud Dextrose Agar 4 %, Potato Dextrose Agar, Defined medium and Colloid Chitin 1 % medium. The highers Vr were 79, 76, 79, 75 µm/h respectively, with aW = 1. The maximum conidia production (3.6x109 conidia/plate) was reached with Sabouraud Dextrose Agar 4 % at aW=0.994. Conidia production decreased as a function of aW, in fact differences of one magnitud order were observed between aW extremes. Maximum conidia density was 6.9 x 108 conidia/cm2 reached with colloidal chitin and aW = 0.973. The medium compotition effect was showed over Vr and conidia production, the best results were obtained with complex media. In solid state fermentation maximal yield was 1.15 x 1010 conidia/gdss, this value was obtained with a moisture content of 66 % (aW = 1), however, yield reduced as moisture content increased. In addition, the use of substrates mixes (wheat bran and sugar cane baggase) higher yields were obtained with media containing only wheat bram, in fact the presence of sugar cane as a texturizer reduced in conidial yields, however real yields (conidia per gram of wheat bran) did not show any stadistical difference in all mixtures. When differents levels of inocula (1x106 , 7x106 , 5x107 conidia/gdss) were tested, similar yields were observed (1 x 1010 conidia/gdss), but time at which this yield was reached (t10) was reduced as inoculum increases; t10 was proposed as fermentations quality parameter. Viability values in at times with the highest yield (1 x 1010 conidia/gdss) were 77.5, 61 and 54% for inocula of 1x106 , 7x106 , 5x107 conidia/dss, respectively. A inoculum size of 1x106 conidia/dss was selected for further experiments. Gaseous atmosphere was modified after 72 h once mycelia was visible, in oxygen riched atmosphere O2/CO2 (26/0 %) yield of 1x1010 conidia/gdss was obtained, this yield was similar to that reached in normal atmosphere O2/CO2 (21/0 %). Nonetheless, using atmospheres with O2/CO2 ratios of 21/5 % and 16/5 %, yields were substantially reduced: 1.4x109 and 5.8x108 conidia/gdss, respectively. CO2 mixtures showed mycelia disruption at the end of cultures, this was more evident in a atmosphere of O2/CO2 : 16/5 %. Conidial viability was affected when atmosphere was modified, values were 73, 58, 44 and 39 % in O2/CO2 (%) mixtures of 21/0, 26/0, 21/5 and 16/5, respectively. Finally, bioassays were performed using Tenebrio molitor larvae. Maximum mortality (52%) was reached with conidia obtained in a normal atmosphere (O2/CO2,: 21/0) with a 50 lethal time (TL50) of 16.9 d. Atmosphere modification caused a negative effect on Beauveria bassiana virulence, since mortality was equal or less to 20 % in the rest of treatments, Viability and hidrofobicity showed as well a reduction with atmosphere modification. The main conclusions were: 1. Beauveria bassiana is very sensitive to culture media composition and water activity. Better radial extension rates, conidia yields and growth were obtained with complex nitrogen sources and water activity values closer to 1. 2. As a recommendation for production systems, the highest solid state fermentation conidia yields (1 x 1010 cnidias/gdss) were reached with normal atmosphere, wheat bran as a substrate, moisture contents of 66 % (aW = 1), a inoculum zise of 1 x 106 conidia/gdss, with an inoculum age of 10 days. Sugar cane bagaze as texturizer did not show effect over conidia yields. 3. Accumulation of CO2 in culture of Beauveria bassiana should be regarded as a detrimental factor. In this work the presence of CO2 in gaseous atmosphere was a negative effect on fungal growth, yields and conidia viability. A clear relationship between conidia relative hydrofobicity and virulence was no found.; El máximo rendimiento de conidios 1.15 x 1010 conidios/gssi, en fermentación en medio sólido se obtuvo con un contenido de humedad de 66 % y aW = 1, disminuyendo progresivamente en función del incremento del contenido de humedad del soporte. Con la mezcla de substratos (salvado de trigo y bagazo de caña) el máximo rendimiento se obtuvo en los medios que únicamente contenía salvado de trigo, los rendimientos reales (conidios/ g Salvado) no se modificaron sustancialmente, no observandose diferencias significativas entre ellos. Cuando, se evaluaron distintos niveles de inoculo (1x106 , 7x106 , 5x107 conidios/gssi), se observaron rendimientos similares, independientemente del inóculo. La viabilidad en el punto donde se alcanzaron concentraciones de 1 x1010 conidios/gssi, fue de 77.5 (+/- 4.9) 61 (+/- 8.4) y 54 (+/- 1) % respectivamente. Independientemente del nivel de inóculo los rendimientos obtenidos fueron del orden de 1 x 1010 conidios/gssi, variando únicamente el tiempo de producción, por lo que se propusó este tiempo t10 como un parámetro de evaluación de las fermentaciones. También se observó que los mejores valores de viabilidad se obtuvieron con los inóculos menores. Los rendimientos de conidios mostraron comportamientos distintos en las atmósferas evaluadas 21/0, 26/0, 21/5, 16/5 %, por un lado con la mezcla O2/CO2 (26/0 %) se obtuvieron rendimientos similares (1 x 1010 conidios/gssi) a los obtenidos con una atmósfera normal (21/0 %). Pero, cuando se incrementó el CO2 en las mezclas y el O2, (21/5, 16/5 %) el rendimiento de conidios, permaneció prácticamente constante después de la modificación. El máximo rendimiento de conidios para la mezcla 21/5 % fue de 1.4 x 109 conidios/gssi, representó una disminución de prácticamente un orden de magnitud en comparación con el obtenido en una atmósfera normal y con la mezcla 26/0 % (1 x 1010 conidios/gssi), para el caso de la mezcla de 16/5 % el máximo obtenido fue de 5.8 x 108 conidios/gssi y represento una reducción de aproximadamente dos ordenes de magnitud en comparación con la atmósfera normal. Macroscópicamente se observó en las mezclas con CO2 una disminución en la cantidad de micelio en función del tiempo, desapareciendo prácticamente hacia el final de la fermentación, lo que fue mas acentuado para la mezcla 16/5 %. La viabilidad se vió afectada por el incremento de CO2 en la atmósfera, los valores obtenidos en los puntos de mayor producción fueron de 73, 58, 44, y 39 % para las mezclas O2/CO2 (%) 21/0, 26/0, 21/5 y 16/5, respectivamente. Los bioensayos con larvas de Tenebrio molitor, en atmósfera normal, mostraron una mortalidad máxima de 52 %, con un tiempo letal 50 (TL50) de 16.9 d. La modificación de la atmósfera tuvo un efecto negativo, sobre la virulencia de B. bassiana, puesto que para el resto de los tratamientos, los valores obtenidos fueron del orden del 20 % o menores. Los valores de viabilidad e hidrofobicidad se redujeron con la modificación de la atmosfera. Las principales conclusiones que se desprenden de este trabajo son: Beauveria bassiana mostró una sensibilidad hacia la composición de los medios de cultivo y la actividad de agua en caja de Petri, obteniéndose las mejores velocidades de extensión radial, rendimientos de conidios y crecimiento en los medios con fuentes de nitrógeno complejas y con valores de actividad de agua elevados (cercanos a 1). Los máximos rendimientos de conidios (1 x 1010 conidios/gssi) se obtuvieron en fermentaciones con una atmósfera normal, con salvado de trigo como substrato con un contenido de humedad de 66%, una aW = 1 y un inóculo de 1 x 106 conidios /gssi y un tiempo de 10 días, el uso de bagazo de caña como texturizante no tuvo efecto en los rendimientos de conidios por gramo de salvado de trigo. Sin embargo, el rendimiento si disminuyó con respecto al peso de substrato inicial (salvado de trigo más bagazo de caña). El incremento en la concentración de CO2 en la mezcla gaseosa tuvo un efecto adverso sobre el crecimiento, rendimientos y viabilidad de los conidios. A diferencia de otros reportes, no se encontró relación entre la hidrofobicidad relativa de los conidios y su virulencia.